Joubert syndrome: neuroimaging findings in 110 patients in correlation with cognitive function and genetic cause. Issue 8 (13th January 2017) - Poretti, Andrea; Snow, Joseph; Summers, Angela C; Tekes, Aylin; Huisman, Thierry A G M; Aygun, Nafi; Carson, Kathryn A; Doherty, Dan; Parisi, Melissa A; Toro, Camilo; Yildirimli, Deniz; Vemulapalli, Meghana; et al.
Abstract : Background: Joubert syndrome is a clinically and genetically heterogeneous ciliopathy. Neuroimaging findings have not been systematically evaluated in a large cohort of patients with Joubert syndrome in correlation with molecular genetic cause and cognitive function. Methods: Brain MRI of 110 patients with Joubert syndrome was included in this study. A comprehensive evaluation of brain MRI studies for infratentorial and supratentorial morphological abnormalities was performed. Genetic cause was identified by whole-exome sequencing, and cognitive functions were assessed with age-appropriate neurocognitive tests in a subset of patients. Results: The cerebellar hemispheres were enlarged in 18% of the patients, mimicking macrocerebellum. The posterior fossa was enlarged in 42% of the patients, resembling Dandy-Walker malformation. Abnormalities of the brainstem, such as protuberance at the ventral contour of the midbrain, were present in 66% of the patients. Abnormalities of the supratentorial brain were present in approximately one-third of the patients, most commonly malrotation of the hippocampi. Mild ventriculomegaly, which typically did not require shunting, was present in 23% of the patients. No correlation between neuroimaging findings and molecular genetic cause was apparent. A novel predictor of outcome was identified; the more severe the degree of vermis hypoplasia, the worse the neurodevelopmental outcome was. Conclusions: The spectrum of neuroimaging findings in Joubert syndrome is wide. Neuroimaging does not predict the genetic cause, but may predict the neurodevelopmental outcome. A high degree of vermis hypoplasia correlates with worse neurodevelopmental outcome. This finding is important for prognostic counselling in Joubert syndrome.